Identifying the image of God : radical Christians and nonviolent power in the antebellum United States - McKanan, Dan, 1967- (Religion in America series (Oxford University Press), 2002)
Between 1820 and 1860, American social reformers pioneered a 'politics of identification' which portrayed minority and socially excluded groups as both physically vunerable and socially related. This text traces the theme of identification through the literature of social reform.